Money and inflation : a new macroeconomic analysis - Rossi, Sergio, 1967- (Edward Elgar Pub., 2001)
"It is a popular notion that money and output are separate and autonomous entities. Money and Inflation argues that this idea can neither explain the purchasing power of money nor its variations over time, and a new theory is therefore presented in its place." "The book aims to provide the foundations for a new analysis of inflation from a macroeconomic perspective. The role of money is investigated in terms of value, prices, profit, and capital accumulation."--BOOK JACKET.